2018
DOI: 10.1021/acsami.8b15452
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrinic Metal–Organic Framework PCN-224 Nanoparticles for Near-Infrared-Induced Attenuation of Aggregation and Neurotoxicity of Alzheimer’s Amyloid-β Peptide

Abstract: The aberrant aggregation of amyloid-β peptide (Aβ) in the brain has been considered as the major pathological hallmark of Alzheimer's diseases (AD). Inhibition of Aβ aggregation is considered as an attractive therapeutic intervention for alleviating amyloid-associated neurotoxicity. Here, we report the near-infrared light (NIR)-induced suppression of Aβ aggregation and reduction of Aβinduced cytotoxicity via porphyrinic metal-organic framework (MOF) PCN-224 nanoparticles. PCN-224 nanoparticles are hydrothermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(82 citation statements)
references
References 29 publications
(48 reference statements)
4
78
0
Order By: Relevance
“…The divalent metal ions such as Zn, Cu, Co and Cd typically coordinate to TCPP to produce 2D MOFs, while tri-and tetravalent Zr, Fe, Hf or Mn metal ions usually form porphyrinic MOFs with 3D structures. [87][88][89][90] For example, Liu et al have reported the construction of biocompatible nanoscale zirconium-porphyrin metal-organic framework (NPMOF)-based imaging-guided therapy systems (IGTSs) by using a microemulsion strategy and tuning the reaction conditions carefully. 71 The NPMOFs were synthesized via a microemulsion template and the auxiliary ligand method using ZrCl4 metal precursor and 5,10,15,20-tetrakis(4-carboxyl)-21H,23Hporphine (TCPP) ligand as well as benzoic acid as the auxiliary ligand, PEG-6000 as capping agent, and cetyltrimethylammonium bromide (CTAB) as surfactant, in DMF at 120 °C for 24 h that resulted in spindle-like particles.…”
Section: Photosensitisersmentioning
confidence: 99%
“…The divalent metal ions such as Zn, Cu, Co and Cd typically coordinate to TCPP to produce 2D MOFs, while tri-and tetravalent Zr, Fe, Hf or Mn metal ions usually form porphyrinic MOFs with 3D structures. [87][88][89][90] For example, Liu et al have reported the construction of biocompatible nanoscale zirconium-porphyrin metal-organic framework (NPMOF)-based imaging-guided therapy systems (IGTSs) by using a microemulsion strategy and tuning the reaction conditions carefully. 71 The NPMOFs were synthesized via a microemulsion template and the auxiliary ligand method using ZrCl4 metal precursor and 5,10,15,20-tetrakis(4-carboxyl)-21H,23Hporphine (TCPP) ligand as well as benzoic acid as the auxiliary ligand, PEG-6000 as capping agent, and cetyltrimethylammonium bromide (CTAB) as surfactant, in DMF at 120 °C for 24 h that resulted in spindle-like particles.…”
Section: Photosensitisersmentioning
confidence: 99%
“…[106] Under light irradiation, the bPEI@CDs exhibited better effects on the inhibition of Aβ aggregation and the dissociation of Aβ aggregates through the generation of 1 O 2 . [112] The PCN-224 nanoparticles can generate 1 O 2 under NIR irradiation to suppress Aβ monomer aggregation. [107][108][109][110][111] Yang and coworkers chose PCN-224 nanoparticles which were synthesized by coordinating tetra-kis(4-carboxyphenyl)porphyrin (TCPP) ligands with Zr by hydrothermal method (Figure 11).…”
Section: Pdt For Admentioning
confidence: 99%
“…A schematic illustration of bPEI@CDs' capabilities in the inhibition of β-amyloid (Aβ) assembly and disaggregation of preformed fibrillar aggregates. [112] Copyright 2018, American Chemical Society. Reproduced with permission.…”
Section: Aβ Inhibitors For the Therapy Of Admentioning
confidence: 99%
“…24,25 Although not explicitly stated in the literature, it is discussed in the MOF community that syntheses of porphyrinbased Zr-MOFs are notoriously difficult to reproduce, leading to the co-existence of different MOF-525 and PCN-221 protocols. 17,22,[24][25][26][27] In fact, many studies report the same product for different experimental data 21,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] , suggesting that the synthetic protocols and the resulting structures are still not well understood. This is exacerbated by poor quality and insufficient powder X-ray diffraction (PXRD) data making structure assignment ambiguous.…”
Section: Introductionmentioning
confidence: 99%